2017
DOI: 10.1093/femsre/fux018
|View full text |Cite
|
Sign up to set email alerts
|

Microbial processes driving coral reef organic carbon flow

Abstract: Coral reefs are one of the most productive ecosystems on the planet, with primary production rates compared to that of rain forests. Benthic organisms release 10-50% of their gross organic production as mucus that stimulates heterotrophic microbial metabolism in the water column. As a result, coral reef microbes grow up to 50 times faster than open ocean communities. Anthropogenic disturbances cause once coral-dominated reefs to become dominated by fleshy organisms, with several outcomes for trophic relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 230 publications
1
72
0
2
Order By: Relevance
“…In the case of Saba Bank, dissolved inorganic nutrients were depleted in the near-surface layer where the shallow water coral reefs are located. Below this layer, however, nutrient concentrations steadily increased down to −600 m. The low near-surface nutrient levels are in line with reports starting as early as Darwin's observation that coral reefs thrive in nutrient poor waters ('Darwin's paradox') with their productivity being sustained by efficient recycling pathways and their net import and export being very low (Silveira et al, 2017). Several hypotheses have been put forward to explain this apparent paradox such as the 'sponge-loop' (de Goeij et al, 2013) and the 'island mass effect' (Gove et al, 2015).…”
Section: Internal Wave Observations Off Saba Banksupporting
confidence: 86%
“…In the case of Saba Bank, dissolved inorganic nutrients were depleted in the near-surface layer where the shallow water coral reefs are located. Below this layer, however, nutrient concentrations steadily increased down to −600 m. The low near-surface nutrient levels are in line with reports starting as early as Darwin's observation that coral reefs thrive in nutrient poor waters ('Darwin's paradox') with their productivity being sustained by efficient recycling pathways and their net import and export being very low (Silveira et al, 2017). Several hypotheses have been put forward to explain this apparent paradox such as the 'sponge-loop' (de Goeij et al, 2013) and the 'island mass effect' (Gove et al, 2015).…”
Section: Internal Wave Observations Off Saba Banksupporting
confidence: 86%
“…Only a few studies have specifically considered Symbiodiniaceae‐bacterial interactions in the coral holobiont, with their results pointing to the potentially critical role that these partnerships might play in regulating holobiont nutrient cycling and competitive fitness (Ritchie, ; Bourne et al ., ; Ainsworth et al ., ; Peixoto et al ., ; Silveira et al ., ; Bernasconi et al ., ); Table ). For example, some coral‐associated bacteria can rapidly take up organosulfur compounds released by Symbiodiniaceae cells, such as dimethylsulfoniopropionate (DMSP), to sustain their growth and produce an antimicrobial compound active against common coral pathogens (Raina et al ., ; Raina et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have demonstrated that both endosymbiotic Symbiodiniaceae and associated bacteria support the persistence of corals through the exchange of metabolites and bioactive compounds (Rohwer et al ., ; Cantin et al ., ; Ainsworth et al ., ; Bourne et al ., ; Glasl et al ., ; Peixoto et al ., ; Hillyer et al ., ; Matthews et al ., ). Yet, remarkably, the role of bacteria in regulating Symbiodiniaceae resource acquisition, competitive performance and functional diversity (as both free‐living and endosymbionts) is relatively unexplored (Ritchie, ; Bourne et al ., ; Ainsworth et al ., ; Peixoto et al ., ; Silveira et al ., ; Bernasconi et al ., ); Table ). This fundamental gap in knowledge wholly constrains our understanding of how microbes act in concert to regulate the health of coral holobionts, especially given the importance of bacterial‐algal interactions for nutrient cycling, signal transduction and gene transfer as demonstrated for other microalgal taxa (Seymour et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the mucus produced by corals and other benthic organisms (Silveira et al. ), which is released to the surrounding environment, can be consumed by sponges (Rix et al. , ), and is also a carbon source for microbes, upon which sponges can subsequently feed.…”
Section: How Might Other Changes On Reefs Directly or Indirectly Inflmentioning
confidence: 99%